Aestheticism and ethicism: the history of one prophecy: Aestheticism and ethicism: the history of one prophecy - Kalashyan, Marina (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
This article is devoted to the questions of existential being in the 21st century. An attempt has been made to reveal the anthropological specifics of the epoch through the prism of its ethical and aesthetic dimensions. The methodological basis of the analysis was the ethical-aesthetic dichotomous concept of Søren Kierkegaard. As a result of the historical and philosophical analysis of the correlation between ethical and aesthetic worldviews, it is concluded that the prevailing nowadays aesthetic mode of being as "being-with-itself" is not non-alternative. The thesis is supported that both the ethical attitude toward "being-with-others" and the aesthetic attitude toward "being-with-itself" are generated by a common for both ideology of subjectivism.
Keywords: Կյերկեգոր; բարոյագիտություն; գեղագիտություն; ընտրութուն; հետմոդեռնիզմ